Polyolefin-derived substrate-grown carbon nanotubes as binder-free electrode for hydrogen evolution in alkaline media - Wu, Xinyi (2024)
Switching from a linear mode of waste management to a circular loop by transforming plastic waste into carbon nanotubes (CNTs) is a promising approach to current plastic waste treatment. One of the many applications of CNTs is its use for electrocatalytic water splitting for hydrogen evolution. Existing methods of CNTs-based hydrogen evolution reaction (HER) electrode fabrication involve additives like polymeric binders and additional steps to improve CNT dispersion, which are detrimental to the CNT structure and properties. The in-situ fabrication approach can potentially be a one-pot solution to HER electrode synthesis. In this study, polyolefins pyrolysis gas and a Co:Ni:Mg catalyst were used to fabricate binder-free CNTs-based electrodes on different substrates for HER. The study assessed CNT quality on conductive carbon paper, semiconductive silicon, and dielectric glass substrates, evaluating their HER performance in 1 M KOH. A mixture of hollow-core, bamboo-like, and cup-stacked arrangement nanotubes were synthesized on the substrates, with CNTs on glass and carbon paper substrates possessing better graphitization than CNTs grown on silicon. This is in agreement with HER performance, whereby the as-prepared electrodes required overpotentials of 267 mV, 241 mV, and 216 mV for silicon, glass, and carbon paper, respectively, to achieve 10 mA/cm2. Despite being poorly conductive, the glass substrate electrode achieved a lower overpotential than the silicon electrode. Additionally, the as-prepared silicon electrode faced a delamination issue likely attributed to the lower surface energy of the silicon substrate surface, demonstrating the weaker adhesion between the CNTs and silicon surface. The proposed approach thus showed that the in-situ fabricated electrodes performed better than separately synthesized CNTs prepared into electrodes by 27.4% and 14.2% for carbon paper and glass substrates, respectively. The improved performance of the as-prepared, binder-free electrodes can be linked to the lower charge-transfer resistance and reduced contact resistance between the CNTs and substrate.